(untitled) (Journal of Intellectual Property Rights (JIPR), 2023)
Capital has been a major cause of concern amongst entrepreneurs across the globe. Not everyone enters the professional setting with a bag full of money, neither did the Ambani’s nor did the TATA group. It was not just investments into fruitbearing funds but also loans that have made them superpowers in the market, today. A loan requires one to offer collateral against the principal amount, this collateral is often referred to as security in common parlance. We most often offer tangible assets such as gold, land, car, etc. as security, however, can an intangible asset such as intellectual property also be offered as bank security? This question is dealt with at length by the authors while discussing the legal discourse in India and other developed countries.The authors have collected insights from theearlier cases where intellectual property was offered as security (more specifically as collateral) and analyzed its legal implications in the long run.